2020
DOI: 10.22541/au.160193902.29623129/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of the ionic antineoplastic agent Cytoreg on blood chemistry in the Wistar rat model

Abstract: Cytoreg is an ionic therapeutic agent comprising a mixture of hydrochloric, sulfuric, phosphoric, hydrofluoric, oxalic, and citric acids. In diluted form, it has demonstrated efficacy against human cancers in vitro and in vivo. Although Cytoreg is well tolerated in mice, rats, rabbits, and dogs by oral and intravenous administration, its mechanism of action is not understood. The acidic nature of Cytoreg could potentially disrupt the pH and levels of ions and dissolved gases in the blood. Here, we report the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In vitro and in vivo studies have shown Cytoreg to have oncolytic activity [ [2] , [3] , [4] , [5] ]. In Wistar rats, oral administration of Cytoreg is well tolerated [ 6 ] and was recently shown to increase arterial blood oxygen pressure (pO 2 ) by iv administration [ 7 ]. We became interested in the potential use of Cytoreg topical solution for the treatment of diabetic foot ulcers, owing to the possible improvement of oxygenation to the damaged tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo studies have shown Cytoreg to have oncolytic activity [ [2] , [3] , [4] , [5] ]. In Wistar rats, oral administration of Cytoreg is well tolerated [ 6 ] and was recently shown to increase arterial blood oxygen pressure (pO 2 ) by iv administration [ 7 ]. We became interested in the potential use of Cytoreg topical solution for the treatment of diabetic foot ulcers, owing to the possible improvement of oxygenation to the damaged tissue.…”
Section: Introductionmentioning
confidence: 99%